A comparison between English demonstratives and Vietnamese demonstratives in argumentative essays - Nguyen, Nguyet Minh (Universitas Pendidikan Indonesia, 2022)
In English and Vietnamese, demonstratives are considered one of the most important linguistic items for their ability to enhance writing coherence. Crucial as they are, few investigations have been conducted to analyze the differences in their uses in English and Vietnamese written discourse. This research attempts to investigate the differences in the use of Vietnamese demonstratives and English demonstratives in model Vietnamese (MV) and model American English (MA) argumentative essays. Adopting both quantitative and qualitative analyses, it focuses on the frequency and pragmatic uses of proximal and distal demonstratives in the two languages. It was discovered that English essays had significantly more proximal and cataphoric uses of demonstratives than Vietnamese essays. While English proximal demonstratives this(these) indicated topic shifting and distal demonstratives that(those) signaled topic continuity, a contrary pattern was observed in Vietnamese. Moreover, in investigating the referential uses of demonstratives, it was revealed that the use of Vietnamese demonstratives differed from English in the sense that they could act as discourse connectives facilitating the interpretation process of the readers. The study’s results contribute to the cross-language analysis and comparison of demonstratives and provide implications for the teaching of English demonstratives in academic writing in Vietnam.